Disney after dark - Pearson, Ridley (New York : Disney/Hyperion Books, 2009)
Finn Whitman and his fellow DHIs, teenagers chosen to serve as actors for a new technology, investigate strange occurrences at Disney theme park attractions, racing to uncover a supernatural force that could destroy the world.
Originally published: New York : Disney Editions, c2005.
Accelerated Reader AR
Keywords: Cartoon characters -- Juvenile fiction; Holography -- Juvenile fiction; Good and evil -- Juvenile fiction; Walt Disney World (Fla.) -- Juvenile fiction; Young adult fiction; Adventure fiction; Suspense fiction; Fantasy fiction